Dilema Hubungan Patron-Client Di Komunitas Petani Garam (Studi Kasus di Gampong Cebrek, Kecamatan Simpang Tiga, Kabupaten Pidie, Nanggroe Aceh Darussalam) - Ibnu Phonna Nurdin; Lala M. Kolopaking; Saharuddin . (Institut Pertanian Bogor, 2016)
Gampong Cebrek is the largest salt producer in Pidie district with a total of 1859.53 tons in the year 2013 of the total district production 3397.66 tons, 1763.93 tons in 2014 from the total district production 4020.25, rising to 2762.23 tons in the year 2015 from the total district production 7543.77 tons. Behind the high salt production, farmers are in a state sandwiched cultivate its business due to unfavorable weather and marketing of salt that does not favor them. Therefore, farmers are looking for patrons who can guarantee their lives. This study used a qualitative approach with a total of 10 informants. A research technique used observation and interview. Results showed members of the farming community in Cebrek be divided into two categories: a. Farmers Capital and b. farmers do not have the capital. Generally, farmers who own capital patron-client relationship with: mugee (middlemen), retailers and consumers.Connection is established fairly balanced, so that it can be said patron-client collaborative interwoven. Meanwhile, farmers who do not have the capital, patron-client relationship with toke (middlemen). Patron-client relationshipsmore profitable patron, and hurt farmers salt. It can be concluded that the relationship is exploitative. Kata Kunci : Collaborative, Community, Exploitation, Patron-client, Salt farmers.